NUMERICAL SOLUTION OF PERTURBATION STURM-LIOUVILLE PROBLEMS USING CHEBYSHEV POLYNOMIAL - Khirallah, Mustafa Q. (European Scientific Journal, ESJ, 2013)
In this paper, a boundary value problem which consists of the integro-differential equation is considered, Chebyshev polynomial is used to find the numerical solution of perturbation Sturm-Liouville problems, an example of numerical results are given and algorithms are performed by Mathmatica (0.7) program.